Assessing the impact of climate change on smallholder farmers’ crop net revenue in Togo - Gadédjisso-Tossou, Agossou; Egbendewe-Mondzozo, Aklesso; Abbey, Georges A. (Journal of Agriculture and Environment for International Development (JAEID), 2016)
This study employs a Ricardian modelling approach to measure the impact of climate change variables such as temperature and rainfalls on smallholder famers’ crop net revenue in Togo. The obtained results show that climate has a nonlinear effect on crop net revenue. In rainy season, the marginal impact of temperature on farmers’ net revenue is negative, while the impact of rainfalls is positive. The scenarios of decrease of rainfalls and/or increase of the temperature show negative impacts on the agriculture of Togo given the already harsh climatic conditions in the country. Other variables such as educational attainment, access to extension services and livestock ownership are found to have positive impact on farmers’ crop net revenue. Consequently, policies aimed at improving those factors could improve smallholder farmers’ wellbeing.